Phase Field Modeling of Coalescence of AlSi10Mg Particles in Direct Metal Laser Sintering - Nandy, Jyotirmoy; Sahoo, Seshadev; Sarangi, Hrushikesh; Kalyan Panda, Bibhu (International Journal of Engineering and Technology, 2018)
Direct metal laser sintering (DMLS) is amongst the most proficient technologies in the field of additive manufacturing which produces high quality products. The physical properties of the final products is immensely affected by the process parameters of the process. Being a fast process, the solidification rate is very fast as powdered materials sinter into crystalline structures with the application of laser power. Since the past few decades, computational modeling has helped researchers to predict and optimize the quality of output products. In this study, phase field modeling has been used to study the sintering mechanism and importance of neck growth of AlSi10Mg in DMLS process. Using temperature as an input parameter to study neck growth in equal andÂ  unequal sized particles, it is found that the rise in temperature leads to higher neck growth. It has been found that unequal sized particles experience faster sintering due to high diffusion rate. Also, by increasing the laser power, it has been found that the sintering rate is faster.Â Â